(Re)presentation and supposition. (2002) - Jong, Taeke de
Before a design is drawn, a programmme of demands can be the object of empirical research and after realisation also its evaluation. Is the design in between science itself? If science concerns making more explicit pre-suppositions of thought and investigating them, then design could be scientific. There is a direct relation between designing and varying suppositions within a representation. This article looks for such starting-points for scientific research by design. They do not have to be the same as in empirical research. A technical science may use an assumption of possibility instead of probability. Technically scientific here is defined as: concerning a scientific way of thinking not only taking empirism as a starting-point, but also a not yet existant (possible) design. The article ends by defining context as the set of suppositions that can be varied as well as the object to be designed. This results in a classification of empirical design research and types which are not fully empirical research by design.